1984
DOI: 10.1210/jcem-59-6-1088
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aromatization Stimulates Luteinizing Hormone and Testosterone Secretion in Adult Male Rhesus Monkeys*

Abstract: Experiments were conducted to examine the role of aromatization in the control of LH and testosterone secretion in adult male rhesus monkeys. Treatment of male monkeys (n = 7) with sc Silastic packets containing the aromatase inhibitor 1,4,6-androstatriene-3,17-dione (ATD) resulted in 1.5- to 3-fold elevations in serum LH and testosterone concentrations in six of seven animals. Concurrent treatment of ATD-treated monkeys with small quantities of estradiol-17 beta (n = 4) abolished the stimulatory effect of ATD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 43 publications
4
30
0
1
Order By: Relevance
“…The authors of that study concluded that both testosterone and oestradiol had a role in the negative feedback regulation of LH. This conclusion is consistent with the finding that suppression of aromatisation results in increases in LH concentrations in men, primates and dogs (Ellinwood et al 1984, Juniewicz et al 1988, Bhatnagar et al 1992, Trunet et al 1993, Plourde et al 1994. The situation in the rat was believed to be different, as short-term administration of non-steroidal aromatase inhibitors failed to alter serum LH concentrations; FSH concentrations were not measured in either study (Bhatnagar et al 1992, Plourde et al 1994.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The authors of that study concluded that both testosterone and oestradiol had a role in the negative feedback regulation of LH. This conclusion is consistent with the finding that suppression of aromatisation results in increases in LH concentrations in men, primates and dogs (Ellinwood et al 1984, Juniewicz et al 1988, Bhatnagar et al 1992, Trunet et al 1993, Plourde et al 1994. The situation in the rat was believed to be different, as short-term administration of non-steroidal aromatase inhibitors failed to alter serum LH concentrations; FSH concentrations were not measured in either study (Bhatnagar et al 1992, Plourde et al 1994.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, several studies involving the inhibition of aromatisation have shown a consistent and rapid increase in testosterone concentrations (50%) in humans (Bhatnagar et al 1992, Trunet et al 1993, Hayes et al 1999, primates (Ellinwood et al 1984, Dukes et al 1996, Shetty et al 1998 and dogs (Juniewicz et al 1988). In the present study, an increase in plasma testosterone concentrations occurred within 1 week of anastrozole treatment and was maintained for approximately 5 months but not beyond this time.…”
Section: Discussionsupporting
confidence: 70%
“…Much evidence suggests that oestradiol, formed via aromatization of circulating testosterone, contributes to the regulation of LH secretion in males of several other species including the sheep (Schanbacher, 1984), dog (Worgul et al, 1981), and rhesus monkey (Ellinwood et al, 1984), but not the rat (Krey et al, 1982). Evidence from the ferret and rhesus monkey suggests that oestradiol produced by neural aromatization in the male may ultimately inhibit LH secretion as a result of its action on GnRH neurones in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Primates, and macaques in particular, are more like dogs than rats in that their LH pulses are followed closely in time by a surge of T, and there are significant circadian differences in LH and T secretion, which are much higher at night than during the light hours (Plant 1981;Puri et al 1980;Steiner et al 1980;Steiner and Bremner 1981). Also like dogs, male macaques use E2 for the central feedback of peripheral hormones (Ellinwood et al 1984;Roselli and Resko 1990). The significant diurnal differences and the value of each experimental primate make it much more likely that blood will be sampled without terminating the animal.…”
Section: Measuring T and Lhmentioning
confidence: 99%